Ghana : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This is the third Annual Progress Report on the implementation of the Ghana Poverty Reduction Strategy (GPRS). Both the budget and the GPRS propose to tackle issues including reduction in the domestic debt, reduction of inflation to single digits, increasing revenue mobilization, curtailing deficit financing, and rationalization of expenditure through effective monitoring. The disbursement of the District Assemblies' Common Fund (DACF) has improved. The macroeconomic indicators show that targets set by the government have been achieved, which has led to a stable economic environment.